ANALISIS PENGARUH PAPARAN FISIK PADA SAMPEL GIGI TERHADAP HASIL KUANTIFIKASI DNA FORENSIK MENGGUNAKAN METODE KIT PURIFIKASI DNA KOMERSIAL - Arini, Septi; Budi Witarto, Arief; Betaria Aritonang, Setia (Jurnal TAMBORA, 2021)
Physical exposure to biological samples has an enormous influence on the results of forensic DNA analysis. The lack of molecular research on the effect of physical exposure on dental samples is the reason for the need for further research. This study aims to determine the effect of physical exposure on dental samples on the results of forensic DNA quantification. The parameter used is the concentration value of isolated DNA obtained from real time PCR analysis. The use of real time PCR allows the detection and quantification of specific sequences of DNA samples at the same time to be analyzed. The dental samples used were obtained from different individuals. Teeth are used as identification media because teeth are the hardest part of the body and are chemically the most stable and most resistant to degradation and decomposition. The method in this study is to give three types of treatment to the tested samples in the form of sea water immersion, river water immersion and exposure to free air at room temperature with each treatment consisting of three test samples. All samples were extracted using a Commercial DNA purification KIT with a reagent in the form of a Qiagen KIT (QIAamp® DNA Investigator) then a quantification process was carried out to see the value of the DNA concentration of each sample using real time PCR. The results of DNA quantification of dental samples from each treatment showed that the highest sample concentration value was based on the average of each treatment, namely samples with treatments exposed to free air at room temperature with a concentration value of 1.34 ng/µl, followed by samples soaked using river water with a concentration value of 0.15 ng/µl, while the sample with the lowest concentration is shown by a sample treated with seawater immersion with a concentration value of 0.10 ng/µl. Physical exposure in the form of exposure to free air, exposure to river water and exposure to sea water on dental samples, gave a not too significant effect on the results of DNA quantification produced.